SUFISTIC AND TRANSFORMATIVE PEDAGOGIC VALUES IN SYAIKH SITI JENAR NOVEL BY AGUS SUNYOTO GENETIC STRUCTURALISM - Riadi, Sugeng; Emzir, Emzir (INTERNATIONAL JOURNAL OF LANGUAGE EDUCATION AND CULTURE REVIEW, 2015)
This research aims to know and understand more deeply about mystical values and transformative pedagogic values in the Syaikh Siti Jenar novel written by Agus Sunyoto. The focus of this study was the intrinsic and extrinsic structure of meaning in the novel. The method applied in this study is Â content analysis Â using genetic structure by Lucien Goldmann. The results of the study show a number of sufistic values and transformative pedagogic values. Sufistic values include: repentance, ascetic, indigent, patience, gratitude, pleasure, and trust. While the transformative pedagogic values include altruism, egalitarian, pluralism, and eclectic. The findings of the authors world view includes figures deconstruction of the teachings of Syaikh Siti Jenar, cultural missionary endeavor, the concept of superhuman, mystical literature, and literary history.